The Corrosion Inhibition Effect on Fatigue Behavior for Aluminum Alloy 5052 in the Saline Environment - Eldwaib, Khalid; Aldarwish, Mustafa; Ballem, Mohamed; Garrab, Salem; Adrwish, Salahadin (Journal of Pure & Applied Sciences, 2022)
The corrosion inhibition of Al alloys is the subject of huge technological importance wing to the use of these alloys in wide industrial applications. Fatigue life (number of cycles to failure Nf) for Al-Mg alloy in 3.5% NaCl at different acidity and alkalinity and 3.5% NaCl (pH=1) with inhibitors was investigated in this study. The inhibitors were composed mainly of phosphate, adding a certain proportion of other nontoxic inhibitors to select alternatives to environmentally hazardous chromate. Fatigue behavior was studied by using the corrosion fatigue machine with plane-bending mode. The large difference between the fatigue life in the corrosive mediums, such as NaCl, and that in dry air is noticed. The results showed that in 3.5% NaCl without inhibitor, the minimum fatigue life is obtained at pH=1, where the media is too aggressive (extremely acidic), whereas the highest value is obtained at pH=5 where the very low solubility of oxide film on the alloy. As the concentration of inhibitor increased the number of cycles was increased as well. The scanning electron microscope (SEM) had conducted on the surface morphology and fracture section of the specimens for characterizing.